If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4z+4)-9=39
We simplify the equation to the form, which is simple to understand
2(4z+4)-9=39
Reorder the terms in parentheses
+(+8z+8)-9=39
Remove unnecessary parentheses
+8z+8-9=+39
We move all terms containing z to the left and all other terms to the right.
+8z=+39-8+9
We simplify left and right side of the equation.
+8z=+40
We divide both sides of the equation by 8 to get z.
z=5
| 2x+4y=106 | | (x*x)-6x=0 | | 92*67*67*67*98*75*57*23*34= | | 5y+6=6y-14 | | 2/5b-6-2 | | ln(3x-18)=8 | | 2(2x+2)=4x+6-2 | | (x^2-5)(x^2-4x+5)=0 | | 12x+12-x-5=92 | | 106=41(2x+4y) | | 5+x=87 | | 2-k=0 | | 2(x^2-5)(x^2-4x+5)=0 | | a^2+a+a^2=0 | | 36/3/5 | | 155.00x+7500.00=92440.00 | | X*2+5=-14 | | 39.55+0.20m=80 | | x^(2/3)-1 | | 15+3=18y | | 5b+3(4+5b)= | | x^2=7-2x | | 2x^7-16x^6+12x^5= | | 5+3(4+5)= | | (-15/2)(-1) | | 7x+1x=28+9x | | (324*80)= | | 2x^4-8x^3+40x-50=0 | | 7x+1x=14+9x | | 2.583+(-5.399)= | | 7x+1x=28+9 | | 3x/5-9=27 |